Fever dream : a novel - Schweblin, Samanta, 1978- (Riverhead Books, 2017)
"A young woman named Amanda lies dying in a rural hospital clinic. A boy named David sits beside her. She's not his mother. He's not her child. Together, they tell a haunting story of broken souls, toxins, and the power and desperation of family. Fever Dream is a nightmare come to life, a ghost story for the real world, a love story and a cautionary tale. One of the freshest new voices to come out of the Spanish language and translated into English for the first time, Samanta Schweblin creates an aura ofstrange psychological menace and otherworldly reality in this absorbing, unsettling, taut novel"--